Fallow Land Enhances Carbon Sequestration in Glomalin and Soil Aggregates Through Regulating Diversity and Network Complexity of Arbuscular Mycorrhizal Fungi Under Climate Change in Relatively High-Latitude Regions - Yang, Yurong; Luo, Wenbo; Xu, Jiazheng; Guan, Pingting; Chang, Liang; Wu, Xuefeng; Wu, Donghui (Frontiers in Microbiology, 2022)
Soil aggregation and aggregate-associated carbon (C) plays an essential function in soil health and C sequestration. Arbuscular mycorrhizal fungi (AMF) are considered to be primary soil aggregators due to the combined effect of extraradical hyphae and glomalin-related soil proteins (GRSP). However, the effects of diversity and network complexity of AMF community on stability of soil aggregates and their associated C under long-term climate change (CC) and land-use conversion (LUC) in relatively high-latitude regions are largely unexplored. Therefore, an 8-year soil plots (with a 30-year cropping history) transplantation experiment was conducted to simulate CC and LUC from cropland to fallow-land. The results showed that Glomus, Paraglomus and Archaeospora were the most abundant genera. The diversity of AMF community in fallow-land was higher than cropland, and increased with increasing of mean annual temperature (MAT) and mean annual precipitation (MAP). Fallow-land enhanced the network complexity of AMF community. The abundance families (Glomeraceae and Paraglomeraceae) exhibited higher values of topological features and were more often located in central ecological positions. Long-term fallow-land had a significantly higher hyphal length density, GRSP, mean weight diameter (MWD), geometric mean diameter (GMD) and C concentration of GRSP (C-GRSP) than the cropland. The soil aggregate associated soil organic carbon (SOC) was 16.8%, 18.6% and 13.8% higher under fallow-land compared to that under cropland at HLJ, JL and LN study sites, respectively. The structural equation model and random forest regression revealed that AMF diversity, network complexity and their secreted GRSP mediate effects of CC and LUC on C-GRSP and aggregate associated SOC. This study elucidates the climate sensitivity of C within GRSP and soil aggregates which response symmetry to LUC, and highlights the potential importance of AMF in C sequestration and climate change mitigation.